2020
DOI: 10.1038/s41467-020-18762-5
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 and TGFß cooperativity drives non-canonical Hedgehog signaling in resistant basal cell carcinoma

Abstract: Tumor heterogeneity and lack of knowledge about resistant cell states remain a barrier to targeted cancer therapies. Basal cell carcinomas (BCCs) depend on Hedgehog (Hh)/Gli signaling, but can develop mechanisms of Smoothened (SMO) inhibitor resistance. We previously identified a nuclear myocardin-related transcription factor (nMRTF) resistance pathway that amplifies noncanonical Gli1 activity, but characteristics and drivers of the nMRTF cell state remain unknown. Here, we use single cell RNA-sequencing of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 69 publications
3
55
0
1
Order By: Relevance
“…Here, we use multi-dimensional genomics of patient and mouse tumors to identify the transcription factor (TF) network, chromatin accessibility (“epigenetic”) remodeling, and transcriptional output defining BST. We show that the surface markers TACSTD2, LYPD3, and LY6D, previously associated with MRTF-mediated resistance ( Yao et al, 2020 ), extensively cover the morphological and transcriptional cell states of BST. Mechanistically, we identify c-FOS as a central player of BST in mouse and human tumors and show that c-FOS-mediated BST may be partially reverted by EGFR or MAPK inhibitors, offering a therapeutic opportunity and additional insights to prevent tumor plasticity in patients.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Here, we use multi-dimensional genomics of patient and mouse tumors to identify the transcription factor (TF) network, chromatin accessibility (“epigenetic”) remodeling, and transcriptional output defining BST. We show that the surface markers TACSTD2, LYPD3, and LY6D, previously associated with MRTF-mediated resistance ( Yao et al, 2020 ), extensively cover the morphological and transcriptional cell states of BST. Mechanistically, we identify c-FOS as a central player of BST in mouse and human tumors and show that c-FOS-mediated BST may be partially reverted by EGFR or MAPK inhibitors, offering a therapeutic opportunity and additional insights to prevent tumor plasticity in patients.…”
Section: Introductionmentioning
confidence: 76%
“…We first built bulk transcriptomic signatures for BCC and SCC based on the differential gene expression analysis between human BCCs ( Bonilla et al, 2016 ) and SCCs ( Chitsazzadeh et al, 2016 ) ( Figures S1A and S1B ; Table S1 ). We then superimposed these signatures onto single-cell datasets of pooled naive BCCs (nBCCs) and rBCCs processed for tumor epithelial cells as previously shown ( Yao et al, 2020 ; Yost et al, 2019 ). BCC tumor cells harbored significant heterogeneity in terms of BCC and SCC signature enrichment, irrespectively of being naive or resistant ( Figures 1A and S1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies identified novel non-canonical regulation of GLI in various cancers. Especially, nuclear myocardin-related transcription factor in basal cell carcinoma [ 57 ], deregulated GSK3β in colon cancer cells [ 58 ], Ras–Raf–MEK ERK pathway in hepatocellular carcinoma [ 59 ], fibroblast-derived insulin-like growth factor-1 in oral squamous cell carcinoma [ 60 ], MAPK/ERK signaling in lung adenocarcinoma [ 61 ], transcriptionally-active androgen receptors in pancreatic cancer [ 62 ] and SOX2-BRD4 transcriptional complex in melanoma [ 63 ]. Additionally, studies in breast cancer models, EMT cells induce increased metastasis of weakly metastatic, non-EMT tumor cells in a paracrine manner, in part by non-cell autonomous activation of the GLI transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted by the PI3K/AKT signaling pathway, transcription factor AP-1 is constitutively activated in glioma and is important in cell proliferation ( 34 - 37 ) AP-1, which can bind to a common DNA binding sequence, is a heterodimer composed primarily by the FOS and JUN families ( 38 , 39 ) AP-1 activation involves complex processes, such as increased expression or phosphorylation of FOS and JUN ( 40 ) As revealed in Fig 6A , transfection with miR-218 mimics markedly inhibited JNK phosphorylation, while it slightly affected FOS, JUN and total JNK expression in U251 and SHG44 cells Considering that TGFβ1 is a well-known target of AP-1 ( 41 - 43 ), it was hypothesized that miR-218 could downregulate TGFβ1 expression by suppressing AP-1 activity As revealed in Fig 6A , transfection with miR-218 mimics decreased TGFβ1 expression in U251 and SHG44 cells compared with the control Collectively, these results indicated that transcriptional activity of AP-1 could be inhibited by miR-218, as supported by the AP-1 luciferase reporter assay ( Fig 6B )…”
Section: Resultsmentioning
confidence: 99%